Chitosan-based delivery systems for plants: a brief overview of recent advances and future directions - Mujtaba, Muhammad; Khawar, Khalid Mahmood; Camara, Marcela Candido; Carvalho, Lucas Bragança; Fraceto, Leonardo Fernades [UNESP]; Morsi, Rania E.; Elsaabe, Maher Z.; Kaya, Murat; Labidi, Jalel; Ullah, Hidayat; Wang, Depeng (Elsevier, 2020)
Chitosan has been termed as the most well-known of these biopolymers, receiving widespread attention from researchers in various fields mainly, food, health, and agriculture. It is a deacetylated derivative of chitin, mainly isolated from waste shells of the phylum Arthropoda after their consumption as food. Chitosan molecules can be easily modified for the adsorption and slow release of plant growth regulators, herbicides, pesticides, and fertilizers, etc. Chitosan as a carrier and control release matrix offers many benefits including; protection of biomolecules from harsh environmental conditions such as pH, light, and temperatures and slow, prolonged release of active ingredients from its matrix consequently protecting the plant's cells from the hazardous effects of burst release. In the current review, we will discuss the recent advances in the area of chitosan application as a control release system. In addition, future recommendations will be made in light of current advancements and major gaps.
Keywords: Chitosan nanoparticles; Slow delivery; Phytohormones; Plants